2015
DOI: 10.1007/s12032-015-0526-x
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of arsenic trioxide in patients with relapsed or refractory malignant lymphoma

Abstract: Limited data have been reported regarding the use of arsenic trioxide (ATO) in the treatment of patients with relapsed or refractory malignant lymphoma; therefore, the present phase II study evaluated the efficacy and toxicity of ATO in such patients. A total of 35 patients were treated with ATO (0.25 mg/kg) infused for 1 h daily, 5 days a week, for a 6-week cycle. Patients were evaluated for the efficacy and toxicity of this regimen. The primary outcome evaluated was the overall response rate (ORR), including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This finding suggests that ATO may be clinically helpful in MCL . Meanwhile, ATO can be considered as a promising treatment for the patients with relapsed or refractory malignant lymphoma . It has been shown that ATO has antiproliferative and proapoptotic effects on pancreatic cancer cell lines .…”
Section: Trace Elements and Cancermentioning
confidence: 92%
See 3 more Smart Citations
“…This finding suggests that ATO may be clinically helpful in MCL . Meanwhile, ATO can be considered as a promising treatment for the patients with relapsed or refractory malignant lymphoma . It has been shown that ATO has antiproliferative and proapoptotic effects on pancreatic cancer cell lines .…”
Section: Trace Elements and Cancermentioning
confidence: 92%
“…74 Meanwhile, ATO can be considered as a promising treatment for the patients with relapsed or refractory malignant lymphoma. 73,74 It has been shown that ATO has antiproliferative and proapoptotic effects on pancreatic cancer cell lines. 75 Regardless of encouraging in vitro evidence, ATO has no activity in patients with pancreatic cancer refractory to gemcitabine.…”
Section: The Role Of As In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only a small number of studies have reported on the therapeutic activity of As 2 O 3 and ATRA in patients with FL, and none of these studies reported any responses that were as impressive as observed in our case. One phase II clinical trial of As 2 O 3 for lymphoid malignancies showed that 0 of 3 patients with FL had a response to arsenic therapy in the frontline disease setting [ 3 ], whereas another phase II trial with 35 patients with relapsed refractory lymphoma (7 with FL) showed an overall response rate of 43%, with a median duration of response of 16 weeks [ 4 ]. There is modest efficacy of arsenic in myeloma, myelodysplastic syndrome, mantle cell lymphoma, and Burkitt's lymphoma [ 5 6 7 ].…”
mentioning
confidence: 99%